Arabic dialects and their role in the Koran (Journal of Human Sciences, 2020)
The Researcher  has explained dialects role  in the Holy Quran in helping know and facilitate Allah's Will  via call upon his worship , the researcher  sees that Arab Dialects  had  a first echo  in favor of the spread of Islam and its extraordinary eloquence that defeated the most eloquent  orators since that time and until nowadays. We conceive that the language is more general and global than the dialect , but it is one of its part , also the Quran's Readings are only known dialects before and after the Revelation of the Quran .In fact , Prophetical Hadiths have shown the great role in terms of dialects and their clarification , also , in easing and facilitating Holy Quran understanding  with all its rules  and teachings and related matters .